answersLogoWhite

0


Best Answer

6x+5=3x+5

5=9x+5

x=0

User Avatar

Wiki User

โˆ™ 2010-10-24 12:20:33
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.71
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
346 Reviews

Add your answer:

Earn +20 pts
Q: 6x plus 5 equals 3x plus 5?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

3x plus 5 equals 6x plus 23 what is x?

3x + 5 = 6x + 23 -3x = 18 x = -6


What is the answer to 4 plus 6x equals 5 plus 3x plus 7?

6x+4=3x+12 => 6x-3x=12-4 => 3x=8 => x=8/3=2.666...


If 6x-7 equals 3x plus 5 what is x?

6x-7 = 3x+5 6x = 3x+12 (subtracting -7) 3x=12 (subtracting 3x) x=4 (dividing by 3)


-3x - 8 plus 6x equals 7?

3x - 8 = 7 so x = 5


What is the solution of 3x-4y equals 1 and 6x plus 12y equals 7?

x = 3/5 and y = 1/5


3x equals 6x-15 then x plus 8 equals?

3x=6x-15 ....you want to take 6x and put it on the other side of the = sign. To do that you do the opposite. So you would subtract since 6x is a positive number. so then the equation is 3x-6x=-15. 3x-6x = -3x which makes the equation -3x=-15. Then you would take -3 which is being multiplied by x and do the opposite operation on the other side. so -3 divided by -15 equals 5. which makes the equation now x=5. So then 5+8=13


12 plus 6x-4 5 plus 2 3x-1?

34x + 72 is the answer to the equation 12 plus 6x-4 5 plus 2 3x-1.


3x plus 5 equals 6x plus 23?

Solve the equation below for x. If your answer is not a whole number, enter it as a fraction in lowest terms, using the slash mark ( / ) as the fraction bar.3x + 5 = 6x + 23x=-6


What is x in 6x-14 equals 3x plus 5?

6x - 14 = 3x + 5Subtract 3x from each side: 3x - 14 = 5Add 14 to each side: 3x = 19Divide each side by 3: x = 19/3


If fx equals 3x-5 then f2 equals?

fx=3x-5 f=(3x-5)/x f2=(6x-10)/x /=divide


What is 2X plus X plus 5 plus 3X-6?

2x+x+5+3x-6=6x-1


6x plus 10 divided by 2?

3x + 5


Substittion for 3x equals y-5 and 2y equals 6x plus 10?

From first equation y = 3x + 5. Substitute this in second equation 2(3x + 5) = 6x + 10 This proves that 6x + 10 = 6x + 10 which is not helpful! I suppose possible solutions would be x = 0, y = 5 or x = 1, y = 8 etc etc Are you sure of your two equations, please?


What must be added to 5 x squred plus 6x plus 9 so that the sum is negative x squered plus 3x plus 3?

5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6


If 3x equals 6x- 15 then x plus 8 equals?

3x = 6x - 15Add 15 to each side:3x + 15 = 6xSubtract 3x from each side:15 = 3xDivide each side by 3:5 = xAdd 8 to each side:13 = x + 8


What is 3x-5 equals 3x plus 5?

3x-5=3x+5 There is no solution.


What is the difference between y equals 3x plus 5 and 6 equals 3x plus 5?

what is a slope


Generating equivalent expression 3x-9 plus 3x plus 5?

The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.


6x plus 4 3x plus 19 what is x?

6x + 4 = 3x + 19 3x + 4 = 19 3x = 15 x = 5 Check it. 30 + 4 = 15 + 19 It checks.


How do you factor 6x square plus 10x?

2x(3x + 5)


What is -6x plus 3y equals -5 as a function?

y=(6x-5)/3


How do you factor 6x squared plus 10x?

6x2 + 10x = 2x*(3x + 5)


What is the answer to the math problem 2 parenthesis 1 minus 3x plus 6 parenthesis equals negative x and show your work?

2(1 - 3x + 6) = -x 14 - 6x = -x 14 - 6x + 6x = -x + 6x 14 = 5x 14/5 =5x/5 14/5 = x


3x plus 5 plus equals 20 what does x equals?

3x+5=20 x=5 since 5x3+5=20


-6x plus 5 equals -31?

6